Application of a nested polymerase chain reaction assay to detect Anaplasma bovis and Anaplasma phagocytophilium in cattle in Lorestan province, Iran - Noaman, V; Beiranvand, M-H (Journal of the Hellenic Veterinary Medical Society, 2022)
Anaplasmosis is an important tick-borne disease caused by Anaplasma species in cattle and other ruminants. This study aimed to determine the leukocytotropic species of bovine anaplasmosis (Anaplasma bovis and A. phagocytophilium) among cattle of Lorestan province, Iran using nested polymerase chain reaction (nPCR). Two hundred blood samples were taken from the jugular vein from healthy cattle, randomly. The extracted from DNA blood cells was screened using the universal primers, which amplify a DNA fragment (1468bp) from the 16S rRNA gene of the genus Anaplasma. The PCR products from positive samples were examined for A. bovis and A. phagocytophilium 16S rRNA gene by species-specific nPCR. Out of the 200 cattle examined, 10 (5%) and 4 (2%) were found nPCR positive for A. bovis and A. phagocytophilium, respectively. No morulae were observed in the blood smears and clinical signs were not seen in infected cattle. Findings in the present study corroborate the low infection rate of A. bovis and A. phagocytophilum in Lorestan province, Iran. Identifying interaction among animal reservoirs, vectors, and pathogens in different climatic zones in Iran are necessary to be performed in future investigations.